Probity Audit as a Monitoring Mechanism: Compliance with Procurement Regulations, Principles and Ethics - Widya Indriani; Eliza Fatima (LPPM Undiksha, 2025)
The main challenge in public procurement lies in the persistent risk of irregularities that undermine transparency, accountability, and integrity. This study aims to evaluate the implementation of probity audits in the procurement process and to analyze the extent to which such audits ensure compliance with regulations, procurement principles, and the application of ethical values. This research adopts a qualitative approach using a case study design at Ministry X, involving internal auditors as the primary subjects. Data were collected through audit document analysis and in-depth interviews and were subsequently analyzed using thematic analysis. The findings indicate that comprehensively implemented probity audits contribute to the principles of good governance by enhancing transparency, accountability, and procurement effectiveness. The audit process not only assesses procedural compliance but also integrates ethical dimensions into procurement practices. However, the implementation of probity audits at Ministry X requires further strengthening, particularly through coverage of the entire procurement cycle, the utilization of technology-based validation mechanisms, greater transparency in determining the Owner’s Estimate (OE), enhanced auditor competencies, and adjustments to supervisory policies. The implications of these findings emphasize that probity audits function as a strategic instrument for institutional reform, integrity enhancement, and the prevention of procurement irregularities. Therefore, probity audits should be positioned not merely as a control mechanism, but as a fundamental pillar of integrity-based public procurement governance.